Akureyri, Iceland - Árnason, Helgi; Reykjavík (Iceland) (North Dakota State University Libraries, Institute for Regional Studies;)
View looking down upon commercial district of Akureyri, Iceland with the Greenland Sea visible in the background. Several boats are visible on the water. Gelatin silver prints; Photographic postcards; 10 x 15 cm. "Akureyri, Iceland, the hometown of Stefansson's ancestors." - typed on label affixed to back of postcard. "80. Akureyri. Island" - printed on front of postcard. Title supplied by staff.